2018
DOI: 10.1002/acr.23455
|View full text |Cite
|
Sign up to set email alerts
|

Trial Characteristics as Contextual Factors When Evaluating Targeted Therapies in Patients With Psoriatic Disease: A Meta‐Epidemiologic Study

Abstract: From this exploratory meta-epidemiologic study, we now have evidence from RCTs to support the notion that patients with PsA are more likely to adhere to targeted therapies compared to patients with psoriasis. Furthermore, we identified a few contextual factors of importance in regard to achieving ACR20 in PsA trials and PASI75 in psoriasis trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 47 As such, the odds of achieving ACR20 response were lower in trials in which a minimum disease duration of 6 months was required, compared with trials in which disease duration was not in the inclusion criteria. 47 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 47 As such, the odds of achieving ACR20 response were lower in trials in which a minimum disease duration of 6 months was required, compared with trials in which disease duration was not in the inclusion criteria. 47 …”
Section: Discussionmentioning
confidence: 98%
“…Results of an exploratory meta-epidemiologic study suggested that certain eligibility criteria have an impact on response to targeted therapies. 47 Prior therapy, disease duration, rheumatoid factor, and use of Classification Criteria for Psoriatic Arthritis criteria for study entry were identified as important contextual factors that may influence the odds of achieving an ACR20 response in PsA trials. 47 As such, the odds of achieving ACR20 response were lower in trials in which a minimum disease duration of 6 months was required, compared with trials in which disease duration was not in the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The term contextual factor is used in different settings without an agreed-upon definition. Contextual factors may be related to prognostic and/or predictive factors 1,2,3 , and may explain heterogeneity in treatment effects. In 2012, the concept of contextual factors was introduced for the development of core outcome sets (COS) within rheumatology.…”
mentioning
confidence: 99%
“…• Inclusion/exclusion criteria: study participants should have similar trial eligibility, such as the same disease and indications for treatment, where they could be randomized to any of the trials in the network [1,4,50]. At the same time, exclusion criteria for comorbidities such as concurrent malignancies and infections should be comparable between studies [31,51,52]. • Clinical trial design and follow-up: clinical trial designs should be comparable [4], with similar treatment durations [3], methods for identifying and measuring treatment outcomes [9] and length of follow-up periods [9].…”
Section: Development Of the Centralized Transitivity Criteriamentioning
confidence: 99%
“…Additionally, Christensen et al [21] potentially detected a modification of the treatment effect based on the disease duration but were unable to demonstrate its independent relative effects from prior DMARD use. Additional PsA, RA and NMA quality guidelines discuss and encourage testing for potential sources of effect modification [5] such as patient comorbidities [51,52] and gender (Consensus Working Party 2013); however, none of the extracted RCTs tested against these potential biases. Furthermore, two full publication NMAs that included apremilast cited variations in study populations and a lack of covariate adjustment in the meta-regressions as limitations; however, potential biases related to transitivity were not measured [18,20].…”
Section: Effect Modificationmentioning
confidence: 99%